Chief-Editor's Note: The role of the family in child education - Navabinejad , Shokoh (Applied Family Therapy Journal (AFTJ), 2023)
The family has the most critical, valuable, and effective roles among all institutions, organizations and social institutions. The family is the most natural and legitimate unit of reproduction and the most comprehensive social unit. The family has educational and social importance. People step into the realm of existence from the family and in the family, and society also comes from the formation of individuals. Therefore, it is one of all society’s main pillars and symbols. The normality or abnormality of society depends on the general conditions of the families, and none of the social harm occurs without the influence of the family. The main and obvious role of the family is reproduction and the transfer of cultural and religious values and heritage from one generation to another. Raising the generation and, providing basic human needs and creating psychological, emotional and social balance in the members are among the importance of the family.In Islam, the family is considered a solid foundation and a fundamental social institution. The family is established through marriage as a contract based on rights and laws based on death and mercy. Forming a family is a covenant and a commitment between a man and a woman, whose purpose is to provide human needs and peace and tranquility to each other. Parenting is mandatory and a social necessity. It is a skill that we must learn before having children so that parent-child relationships are formed properly. Parenting is a set of methods that parents use for the growth and development of their children. The methods play a role in satisfying the needs, learning, behavior, performance, way of thinking, communication, and raising their child. Therefore, it can be said that learning the skills of growth in child rearing is one of the primary and vital foundations of raising children.